Pengaruh Umur terhadap Kualitas Gelatin Tulang Kaki Kambing melalui Pretreatment Asam Asetat (CH3COOH) (Effect of Age on Gelatin Quality of Goat Bones through Pretreatment of Acetic Acid (CH3COOH)) - Hasma - Hasma; Effendi Abustam; Ratmawati Malaka; Muhammad Irfan Said; Rifqi Rifqi (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2020)
The purpose of this study was to determine the effect of the slaughtering age of goats on goat bone gelatin quality. The study was conducted using a completely randomized design (CRD). Data showing influence are further analyzed using the Duncan test. Treatment consisted of age-old 1-year goat bone (T1), 2-year-old goat bone (T2), and 3-year-old goat bone (T3). Each treatment was repeated 3 times. The results showed that the younger the goat age (1 year), the higher the value of yield, protein content, water content, yellowish color level (b), and viscosity. While the fat content, ash content, the level of brightness (L), and redness (a) in the colors show variable results. Each parameter showed a significant effect (P <0.05). Conclusion, 1-year-old goat leg bone gelatin with acetic acid pretreatment (CH3COOH) concentration of 5% has good quality compared to ages 2 and 3 years.